Maximum glacier extent of the Penultimate Glacial Cycle in the Upper Garonne Basin (Pyrenees): new chronological evidence - Fernandes, Marcelo (2021)
The Upper Garonne Basin included the longest glacier in the Pyrenees during the Late Pleistocene. During major glacial advances, the Garonne palaeoglacier flowed northwards along ~ 80 km from peaks of the axial Pyrenees exceeding 2800–3000 m until the foreland of this mountain range at the Loures–Barousse–Barbazan basin (LBBb), at 420–440 m. Here, the palaeoglacier formed a terminal moraine complex that is examined in this work. Based on geomorphological observations and a 12-sample data set of 10Be Cosmic-Ray Exposure (CRE) ages, the timing of the maximum glacial extent was constrained as well as the onset of the deglaciation from the end of the Last Glacial Cycle (LGC). Chronological data shows evidence that the external moraines in this basin were abandoned by the ice at the end of the Penultimate Glacial Cycle (PGC) and the onset of the Eemian Interglacial, at ~ 129 ka. No evidence of subsequent glacial advances or standstills occurred during the LGC in this basin were found, as the few existing datable boulders provided in the internal moraine showed inconsistent ages, thus probably being affected by post-glacial processes. The terminal basin was already deglaciated during the global Last Glacial Maximum at 24–21 ka, as revealed by exposure ages of polished surfaces at the confluence of the Garonne-La Pique valleys, 13 km south of the entrance of the LBBb. This study introduces the first CRE ages in the Pyrenees for the glacial advance occurred during the PGC and provides also new evidence that glaciers had already significantly shrunk during the LGM.